Cancer pharmacology : an illustrated manual of anticancer drugs - Emadi, Ashkan; Karp, Judith E. (Springer Publishing Company, 2024)
"We are living in an exciting time for cancer pharmacology. The fusion of multiple disciplines of basic and clinical science is creating effective, life-prolonging therapies for a growing number of malignancies. The progress is electrifying and the promise for patients is exhilarating!"--